A comparative analysis of cluster based interventions on healthcare-associated infections in a tertiary care hospital in China - Ya Zou; Chuyu Lao; Ting Fan; Tian Wang; Guanwen Lin; Cuiqiong Fan; Yisui Cen; Yukun Lin; Miao Yang; Congrong Li; Zihuan Li (Frontiers in Public Health)
BackgroundHealthcare-associated infections (HAIs) are a significant concern in infection prevention. This study analyzes the trend of incidence of HAIs in a tertiary care hospital in China and assesses the effectiveness of cluster based interventions.MethodsA retrospective analysis was conducted on HAIs reports from 2015 to 2024, focusing on episodes involving the incidence rate of hospital infections, the catheter infection rate related to invasive procedures in the intensive care unit (ICU), healthcare workers’ compliance with hand hygiene, needlestick and sharp injuries (NSIs) among healthcare workers, the prophylactic use rate of antimicrobial agents for Class I surgical incisions, and the antimicrobial usage density (AUD). In 2019, we implemented cluster-based interventions on the incidence of HAIs, strengthening hospital infection control.ResultsThe downward trend in HAIs is notable, with infection rates of 9.34 ± 0.25 and 7.29 ± 0.78 per 1,000 patient-days observed during the periods of 2015–2019 and 2020–2024, respectively (p < 0.001). The decline in ICU infections linked to invasive ventilators and catheters is evident, with significant reductions in ventilator-associated pneumonia rates per 1,000 ventilator days (6.31 ± 1.50 vs. 2.72 ± 1.01, p = 0.002), catheter-associated urinary tract infection rates per 1,000 catheter days (1.66 ± 0.33 vs. 0.99 ± 0.28, p = 0.008), and catheter-related bloodstream infection rates per 1,000 catheter days (1.39 ± 0.35 vs. 0.43 ± 0.14, p < 0.001) during the periods of 2015–2019 and 2020–2024. A significant enhancement in hand hygiene compliance was observed when comparing the periods from 2015–2019 and 2020–2024, with a statistically significant difference (68.13 ± 3.55 vs. 77.39 ± 3.37, p = 0.003). Additionally, a notable decrease in NSIs per 10,000 patient days was observed during the same comparison period, with a statistically significant difference (12.17 ± 1.47 vs. 9.20 ± 1.07, p = 0.006).ConclusionCluster-based interventions are effective in reducing healthcare-associated infections in a tertiary care hospital in China.